The amazing mary jane (2019), volume 1 ebook - Williams, Leah (The Amazing Mary Jane (2019), 2020)
Collects Amazing Mary Jane (2019) #1-5. One lucky lady just hit the jackpot: Mary Jane Watson! MJ finally gets her big shot at a Hollywood starring role - but Mysterio is the auteur director who's cast her, and the film is his twisted take on his own life story! Even if Mary Jane can be persuaded to stay on board a biopic of Quentin Beck, not everybody will be a fan of the project. The Vulture has a bone to pick with his old partner in crime, and he isn't alone - savagely sinister Spidey foes come in sixes! But with Peter Parker miles away in New York City, it's up to MJ to save the day! Mary Jane Watson is no stranger to drama, but her life is about to become a blockbuster!